1990
DOI: 10.1007/bf03183923
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical studies from central Nigeria

Abstract: The people of Kwara State. central Nigeria, depend on natural plant resources oftheir forests for food. medicine. pastoral, domestic. and other cultural and religious needs. This area, one of multi-ethnic status, has remained ethnobotanically unexplored until recently. Our survey among herbalists, herb sellers, tribal priests. and local people recorded medical and other uses of52 species ofplants. This firsthand information points out the importance ofplants to tribal groups and modern people ofcentral Nigeria. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 5 publications
3
33
0
1
Order By: Relevance
“…More recent studies also revealed that the methanol extract of the root bark has analgesic and anti-inflamatory activities [45], proteins, amino acids and antraquinones [14,19,46], sterol, terpenoids, acetogenins [48][49][50][51] diterpenes [52], wax and alkaloids [53,54]. The leaf extracts contains anthraquinones and cardiac glycosides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies also revealed that the methanol extract of the root bark has analgesic and anti-inflamatory activities [45], proteins, amino acids and antraquinones [14,19,46], sterol, terpenoids, acetogenins [48][49][50][51] diterpenes [52], wax and alkaloids [53,54]. The leaf extracts contains anthraquinones and cardiac glycosides.…”
Section: Discussionmentioning
confidence: 99%
“…The plant is reputed to be of great medicinal value and is used in native medicine [12]. It have been used against snake venom [13,14], for chest pain, coughs, anemia, urinary tract infection [15,16], venereal diseases [17,18], anthritis and rheumatism [19], diarrohea and dysentery [20][21][22], against malaria [23], head and body ache [24,25] anti-bacterial [26], against leishmaniasis [27], against typanasomiasis [28], eyelid swelling [29] Antiprotozoan [30], antitumor agent [31,32], molluscisidal [33] antiulcer/antacid, smooth muscle relaxant [34], anthelmintic activity [35] and also for cancer treatment [17,36]. A lot of scientific studies have been done and reported concerning its medicinal values but none so far on skin ailments caused by the fungus Melassezia globosa.…”
Section: Introductionmentioning
confidence: 99%
“…Algumas das espécies apresentam importância econômica, pois fornece o látex usado na produção de goma comercial, madeira de qualidade, matéria-prima para especiarias e frutos comestíveis (Pennington, 1990), além de serem utilizadas na medicina popular para os mais variados fi ns, tais como malária (Bhat et al, 1990), hanseníase (Nwude;Ebong, 1980), febres e resfriados (Gill;Akinwumi, 1986), infl amação ovariana e diabetes (Desmarchelier et al, 1999;Pereira et al, 2004). A literatura reporta para algumas espécies atividades antibacteriana (Kudi et al, 1999;Ogunwande et al, 2001), antifúngica (Ogunwande et al, 2001), antiviral (Khurana, 1972), antitumoral (Suffness et al, 1988), analgésica (Almeida et al, 1985;Pal;Nandy, 1999), tripanosomicida (Muelas-Serrano et al, 2000), antipirética e antiinfl amatória (Pal;Nandy, 1999;Falcão et al, 2005), antiespasmolítica, anticonvulsivante, depressora do SNC e anti-hiperglicêmica (Almeida et al, 1985;Naik et al, 1991;Barbosa-Filho et al, 2005), entre outras.…”
Section: Introductionunclassified
“…The bark of tamarind tree was reported as to have antiinflammatory, analgesic and wound healing properties [9,10] . In West Africa, the macerated fresh bark of the young twigs was used both as a purgative and to relieve abdominal pain [11] .…”
Section: Abstract: Apoptosis Anticancer Cantharidin Caspase Tamamentioning
confidence: 99%
“…The bark of tamarind tree was reported as to have antiinflammatory, analgesic and wound healing properties [9,10] . In West Africa, the macerated fresh bark of the young twigs was used both as a purgative and to relieve abdominal pain [11] .Cantharidin is a colorless, odourless terpene secreted by many species of blister beetles. Cantharidin, isolated from the Chinese blister beetles, Mylabris phalerata or M. cichorii, displays antitumor activity and induces apoptosis in many types of tumor cells.…”
mentioning
confidence: 99%